4, 4′-Difluorobenzhydryl-modified bis(imino)-pyridyliron(ii) chlorides as thermally stable precatalysts for strictly linear polyethylenes with narrow dispersities. Issue 22 (19th May 2020) - Zhang, Qiuyue; Zhang, Randi; Han, Mingyang; Yang, Wenhong; Liang, Tongling; Sun, Wen-Hua
Abstract : Extremely highly active and thermal-stable bis(imino)pyridine-iron precatalysts appended with ( p -FPh)2 CH groups were achieved in ethylene polymerization for highly linear polyethylenes with narrow distributions. Abstract : The 4, 4′-difluorobenzhydryl-modified bis(imino)pyridylferrous chlorides, [2-CMeN(2, 6-(4-FC6 H4 )2 CH2 -4- t -BuC6 H2 )-6-(CMeNAr)C5 H3 N] FeCl2 (Ar = 2, 6-Me2 C6 H3 Fe1, 2, 6-Et2 C6 H3 Fe2, 2, 6-i-Pr2 C6 H3 Fe3, 2, 4, 6-Me3 C6 H2 Fe4, 2, 6-Et-4-MeC6 H2 Fe5 and 2, 6-(4-FC6 H4 )2 CH2 -4- t -BuC6 H2 Fe6 ), were synthesized in good yields. All iron complexes were characterized by 1 H/ 19 F NMR and elemental analysis, and the molecular structures of representative complexes Fe1 and Fe6 were determined by single crystal X-ray diffraction, which revealed a slightly distorted square pyramid around the iron center. Activated with either MAO or MMAO, Fe1–Fe5 exhibited very high activities (up to 17.2 × 10 6 g (PE) mol −1 (Fe) h −1 for Fe1 /MMAO) toward ethylene polymerization, producing highly linear polyethylenes with narrow dispersities as required by industry and value added PEs. Importantly, the Fe1 /MAO maintained an activity of 9.5 × 10 6 g (PE) mol −1 (Fe) h −1 at 100 °C of operating temperature, making the catalytic system suitable for practical application. Simulation quantitatively revealed the mechanism of the enhanced catalytic performance from the electronic and steric point of view.